2013
DOI: 10.4028/www.scientific.net/amr.724-725.1033
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Hydride of Orthorhombic Crystal from High-Energy Ball Milling under Hydrogen Atmosphere

Abstract: The crystal structure of magnesium hydride affects the properties of magnesium for hydrogen storage. The crystal phase and dehydriding temperature of magnesium hydride from magnesium by high-energy ball milling under hydrogen atmosphere with anthracite carbon, which was prepared from anthracite coal by demineralization and carbonization, as milling aid was investigated. The HRTEM observation and XRD characterization showed that the Mg hydrided into nanocrystalline β-MgH2of tetrahedral crystal structure and γ-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…The particle size of the Mg–Ni nanocomposite hydrogenated at 150 °C is about 10–30 nm, which is much smaller than that of MgH 2 prepared by other methods. According to previous studies, the size reduction of MgH 2 could decrease the hydrogen desorption temperature and improve the first hydrogen desorption kinetics. , In addition, γ-MgH 2 phase can destabilize β-MgH 2 and thereby lower the dehydrogenation temperature . Furthermore, Zalusk et al found that the ball-milled mixtures of MgH 2 and Mg 2 NiH 4 exhibited a synergetic effect for the hydrogen desorption .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The particle size of the Mg–Ni nanocomposite hydrogenated at 150 °C is about 10–30 nm, which is much smaller than that of MgH 2 prepared by other methods. According to previous studies, the size reduction of MgH 2 could decrease the hydrogen desorption temperature and improve the first hydrogen desorption kinetics. , In addition, γ-MgH 2 phase can destabilize β-MgH 2 and thereby lower the dehydrogenation temperature . Furthermore, Zalusk et al found that the ball-milled mixtures of MgH 2 and Mg 2 NiH 4 exhibited a synergetic effect for the hydrogen desorption .…”
Section: Resultsmentioning
confidence: 95%
“…52,53 In addition, γ-MgH 2 phase can destabilize β-MgH 2 and thereby lower the dehydrogenation temperature. 54 Furthermore, Zalusk et al found that the ball-milled mixtures of MgH 2 and Mg 2 NiH 4 exhibited a synergetic effect for the hydrogen desorption. 55 Those fine Mg 2 NiH 4 particles on the surface of large MgH 2 grains serve as gateways for hydrogen desorption from the interior of the MgH 2 grains.…”
Section: Hydrogen Sorptionmentioning
confidence: 99%
“…The metastable γ-MgH 2 , belonging to a-PbO 2 -type orthorhombic crystal structure, is usually produced by ball milling (Varin et al, 2006;Ponthieu et al, 2013;Zhou et al, 2015) as well as under high compressive stress (Vajeeston et al, 2006;Siviero et al, 2009;Ham et al, 2013). Zhou et al (2013) pointed out that the H octahedrons surrounding Mg atoms are deformed in the γ-MgH 2 . Besides, the octahedral chain takes a zigzag form, while for the β-MgH 2 , the chain is straight.…”
Section: Sample Characterizationmentioning
confidence: 99%
“…Для магния наряду с тет-рагональным гидридом β-MgH 2 известен также мета-стабильный орторомбический гидрид γ-MgH 2 , форми-рующийся из β-MgH 2 при давлениях в несколько ги-гапаскаль или МА в планетарных мельницах [12,13]. При температурах, близких к комнатной в Mg раство-ряется всего около 1 at.% водорода, а растворимость углерода пренебрежимо мала.…”
Section: Introductionunclassified